2011
DOI: 10.4012/dmj.2011-101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ions release / incorporation of the prototype S-PRG filler-containing endodontic sealer

Abstract: Objective: This study aimed to evaluate a prototype surface reaction-type pre-reacted glass-ionomer (S-PRG) filler-containing endodontic sealer (S-PRG sealer) in terms of its ion-releasing ability and the incorporation of the released ions by root canal dentin. Materials and Methods: The concentration of ions in the set S-PRG sealer was measured by ICPS and with a fluoride ion electrode. Element mapping and chemical component bulk analysis of the outermost dentin of the S-PRG sealer-dentin interface were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 26 publications
1
43
0
1
Order By: Relevance
“…Our study demonstrated that S-PRG released 6 different types of ions throughout all tested time points, which is consistent with previous studies conducted on various S-PRG based materials [16,41]. In addition to the expected antibacterial action of some of the ions released 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 15 by S-PRG, ions like fluoride and strontium may play an important role in apatite formation and stability.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our study demonstrated that S-PRG released 6 different types of ions throughout all tested time points, which is consistent with previous studies conducted on various S-PRG based materials [16,41]. In addition to the expected antibacterial action of some of the ions released 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 15 by S-PRG, ions like fluoride and strontium may play an important role in apatite formation and stability.…”
Section: Discussionsupporting
confidence: 80%
“…It is the most reliable mechanical test that can rank the dislodgment resistance of various endodontic materials applied to dentine such as root canal sealers, root repair materials and intraradicular posts 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 study (7 days), which was selected because it is the common storage time used in the vast majority of studies investigating the push-out bond strength of calcium silicate root cements [25,56]. Fluoride, strontium and silicon ions released from a prototype S-PRG-based root canal sealer were suggested to incorporate into root dentine significantly deeper after one and three months of application compared to one week application [41]. The bond strength of MTA at the apical part of the roots showed a severe and significant drop compared to other locations.…”
Section: Various Chemical Compositions Of Root Repair Materials May Lmentioning
confidence: 99%
“…A recently published study reported that Sr enhances enamel remineralization when used in conjunction with fluoride 28) . Moreover, B, F, and Sr ions released from S-PRG filler may have antibacterial activity 29) , but further analysis of these properties needs to be performed. Cattani-Lorente et al reported that Na is present in the S-PRG filler composition and is released with Al 30) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence indicating that S-PRG fillers release Al, B, F, Na, Si, and Sr ions [8][9][10][11][12][13] . Further, it has been reported that Si, Sr, and F ions released from S-PRG fillers are effective in improving the acid resistance of tooth surfaces [18][19][20][21]35) .…”
Section: Discussionmentioning
confidence: 99%
“…S-PRG fillers release aluminium (Al), boron (B), fluoride (F), sodium (Na), silicon (Si), and strontium (Sr) ions [8][9][10][11][12][13] . Si and F ions are known as strong inducers of remineralization of the dentin matrix [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%